Identification of Early Mobilization Interventions in Cardiovascular Disease Patients in Hospital - Gala, Merry; Syam, Yuliana; Tahir, Takdir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to categorize various early mobilization therapies in heart disease patients. The research method used is a systematic review by searching for articles using the Science Direct, PubMed, and Google Scholar databases. Key phrases included